Juridical Review of the Importance of a Franchise Registration Certificate (STPW) in Franchise Businesses in Indonesia - Purborini, Vivi Sylvia; Suryaningsih, Suryaningsih (Cita konsultindo, 2024)
A franchise must meet the criteria, have business characteristics, be proven to provide profits, have standards for services and goods and/or services offered which are made in writing, easy to teach and apply. Legal awareness is the source of all law. With In other words, legal awareness exists in every human being because every human being has interests, so if the law It is understood and implemented well their interests will be protected and if friction occurs interests, the law is present as an alternative solution. Thus, legal awareness is not only a must have only by certain groups such as law graduates, lawyers,police, prosecutors and judges, but basically it must be owned by every human being without exception so that their interests can be achieved protected. In this research, normative research methods were used. Normative juridical research is a type of library legal research, Legal consequences for franchises that do not have a franchise registration certificate (STPW). does not meet the objective requirements as intended in Article 1320 paragraphs (3) and (4) such as violating the law, public order and morality.